Thermal heterogeneity of carotid arteries as a novel biomarker in patients with diabetes mellitus assessed for coronary artery disease. (1st July 2018) - Tzanis, G.; Bonou, M.; Benetos, G.; Biliou, S.; Liatis, S.; Kapelios, C.; Toutouzas, K.; Tousoulis, D.; Barbetseas, J.
Abstract: Background: Vulnerable plaque plays crucial role in prognosis of diabetes mellitus (DM). Microwave radiometry (MWR) allows measurement of the temperature of tissues, thus indirectly reflecting inflammation, a characteristic of atherosclerotic plaque stability. Aim of the study was to evaluate the relation of carotid artery inflammation with glycemic control and presence of coronary artery disease (CAD). Methods: We included 112 patients (65 ± 9 years, 30 ± 5 kg/m 2, 74 DM and 38 non-DM, with a 2:1 ratio) that were referred for scheduled coronary angiography (CA) for evaluation of their clinical condition. We measured thermal heterogeneity, expressed as temperature difference (ΔT) along each carotid artery, with MWR and maximum temperature difference between the 2 carotid arteries (ΔΤmax). Results: Patients with DM presented higher ΔTmax comparing to patients without DM (0.91 ± 0.29 vs 0.71 ± 0.25 °C, p < 0.001). Glycaemia over time was associated with thermal heterogeneity of carotids (HbA1c: <6.5 : 0.78 ± 0.23, HbA1c: 6.5–7 : 0.87 ± 0.24, HbA1c: 7–8 : 0.99 ± 0.30, HbA1c: >8 : 1.15 ± 0.35 °C, p = 0.003). Patients with CAD presented higher ΔΤmax comparing to patients with normal CA (0.93 ± 0.24 vs 0.68 ± 0.25 °C, p < 0.001) and patients that underwent coronary revascularization presented higher ΔTmax (0.95 ± 0.25 vs 0.76 ± 0.26 °C, p < 0.001). A ΔTmax ≥ 0.9 (received by ROC analysis) was an independent predictor for revascularization in DM patients (odds ratio 3.29, 95% CI: 1.07–10.16; p = 0.039) when adjusted for sex, age and the established risk factors of CAD. Conclusion: Local inflammatory activation of carotid arteries is more pronounced in patients with DM and is associated with the glycemic control. Carotids' thermal heterogeneity is associated with need for revascularization supporting its predictive value in DM patients assessed for CAD.